Structural and spectral studies on benzoyl Thiourea based on DFT calculations (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The experimental and theoretical vibrational spectra of benzoyl thiourea were investigated. The experimental FT-IR (400–4000 cm−1) and FT-Raman spectra (100–4000 cm−1) of the molecule in the powder form were recorded. Theoretical vibrational frequencies and geometric parameters (bond lengths and bond angles) were calculated using density functional B3LYP method with 6-311G++(d,p) and cc-pVDZ  basis sets by Gaussian program, for the first time. The complete assignments were performed on the basis of the potential energy distribution (PED) of the vibrational modes, calculated with scaled quantum mechanical (SQM) method. The formation of the hydrogen bond was investigated using NBO calculations. The electron density-based local reactivity descriptors such as Fukuifunctions were calculated. The calculated HOMO and LUMO energies show that charge transfer occur within the molecule. The dipole moment (μ) and polarizability (α), anisotropy polarizability (Δα) and first order hyperpolarizability (βtotal) of the molecule have been reported